Graves' Disease - Gensure, Robert (IntechOpen, 2021)
Graves' disease is caused by autoantibodies to the thyroid gland that mimic thyroid-stimulating hormone, causing the gland to overproduce thyroid hormone. This speeds the metabolism of the patient and can lead to dangerous conditions including atrial fibrillation and heart failure. Mainstays of treatment have included antithyroid medication, surgical removal of the thyroid gland, and more recently, radiofrequency ablation of the thyroid gland. Advancements in diagnostic testing have enhanced our understanding of the natural course of the disease, creating additional therapeutic options. Enhanced understanding of the autoimmunity behind the disorder may lead to therapeutic options that address the underlying autoimmunity. This book provides a comprehensive review of these enhancements and how they have resulted in changes in common clinical practice.